Hi!
The correct option would be A) Mendel’s genetics states laws that are now part of the theory of biological evolution.
When Darwin proposed the idea of biological evolution, which revolved around the concept that favorable genes are naturally selected into a species to ensure survival, his theory was criticized as during that time there was the idea that individual traits of two parents would present themselves as a blend in the offspring.
Gregor Mendel's theory of inheritance supported Darwin's idea as it dealt with the transmission of traits in generations through entities called genes, which were present in pairs for a particular trait.
Hope this helps!
Answer:
<em><u>172,000 second </u></em>
<em><u>I'M</u></em><em><u> </u></em><em><u>NOT</u></em><em><u> </u></em><em><u>SURE</u></em><em><u> </u></em><em><u>THAT</u></em><em><u> </u></em><em><u>THIS</u></em><em><u> </u></em><em><u>IS</u></em><em><u> </u></em><em><u>RIGHT</u></em><em><u> </u></em><em><u>OR</u></em><em><u> </u></em><em><u>WRONG</u></em><em><u> </u></em><em><u> </u></em><em><u>IF</u></em><em><u> </u></em><em><u>IT'S</u></em><em><u> </u></em><em><u>WRONG</u></em><em><u> </u></em><em><u>THEN</u></em><em><u> </u></em><em><u>SORRY</u></em><em><u> </u></em>
The statement about pointwise convergence follows because C is a complete metric space. If fn → f uniformly on S, then |fn(z) − fm(z)| ≤ |fn(z) − f(z)| + |f(z) − fm(z)|, hence {fn} is uniformly Cauchy. Conversely, if {fn} is uniformly Cauchy, it is pointwise Cauchy and therefore converges pointwise to a limit function f. If |fn(z)−fm(z)| ≤ ε for all n,m ≥ N and all z ∈ S, let m → ∞ to show that |fn(z)−f(z)|≤εforn≥N andallz∈S. Thusfn →f uniformlyonS.
2. This is immediate from (2.2.7).
3. We have f′(x) = (2/x3)e−1/x2 for x ̸= 0, and f′(0) = limh→0(1/h)e−1/h2 = 0. Since f(n)(x) is of the form pn(1/x)e−1/x2 for x ̸= 0, where pn is a polynomial, an induction argument shows that f(n)(0) = 0 for all n. If g is analytic on D(0,r) and g = f on (−r,r), then by (2.2.16), g(z) =
The work done by the machine is equal to the product between the force applied and the distance over which the force is applieds, so in this case:
![W=Fd=(3 N)(9 m)=27 J](https://tex.z-dn.net/?f=W%3DFd%3D%283%20N%29%289%20m%29%3D27%20J)
And the power of the machine is equal to the ratio between the work done by the machine and the time taken: